Comparison of the Nasal Olfactory Organs of Various Species of Lizardfishes (Teleostei: Aulopiformes: Synodontidae) with Additional Remarks on the Brain - L. Fishelson; D. Golani; B. Galil; M. Goren (International Journal of Zoology)
The olfactory organs of lizardfishes (Synodontidae) are situated in two capsules connected to the outside by incurrent and excurrent openings. The olfactory epithelium is in form of petal rosettes each composed of lamellae and a rephe, and bear olfactory receptor neurons, supporting cells and cells with kinocillia. The dimension of rosettes and lamellae, as well as the number of lamellae, increase with growth of the fish; until in adult fish these parameters remaine constant, species specific. In adult Synodus spp. and Trachinocephalus myops the rosettes are 3.5–4.0 mm long, with 5–8 lamellae, whereas in Saurida spp. they are 8.0 mm and possess up tp 22 lamellae. The number of ORN ranges from 2,600 on the smaller lamellae to 20,000 on the largest ones. The number of ORN/mm2 of olfactory is ca. 30,000 in Saurida spp. Thus the rosettes of S. macrolepis with 20 lamellae possess a total of ca. 170,000 ORN, whereas those of Sy. variegatus and T. myops with the average of six lamellae possess only ca. 50,000–65,000 ORN. The olfactory nerves lead from the rosettes to the olfactory balbs situated on the olfactory lobes. The differences among the species in olfactory organs are discussed in correlation with their distribution.